Design of Steel Tower Prototype of 3KW Wind Turbine in Jarmh City - Altaher O. Alreda; Zakareia A. Alarabi; Abduesslam A. Maki (African Journal of Advanced Pure and Applied Sciences, 2022)
To extract energy from wind, wind turbines emerged as one of the most efficient ways of converting the kinetic energy in wind into mechanical power. In order to take advantage of the wind speed increases are available at these heights, and access to design the most efficient and safe or optimization of the structures that support them will become increasingly important for the successful spread of wind power. This study tries to provide the design to create a tower of small wind turbines in rural areas in the South of Libya in the context of limited access for homes or small companies. The objectives of this study are: 1) determination of technical specification of steel tower; 2) general design of tower construction; 3) design support bearings at the top of the tower; 4) design of bearings and calculation its lifetime.The technology of finite element and numerical analysis is used to find different criteria to determine the response of structural and dynamic in terms of the distribution of maximum stress and deflection. Both static and buckling analysis of towers are used; in which static analysis, the loads not varying with time is calculated with analysis of principal stress and Von Mises stresses. Whereas, in buckling analysis, the eigenvalues and the buckling modes are obtained under the axial compressive load, by ignoring otherloads and gravity effects.Based on findings of this study, it can be concluded that the tubular tower with variable diameters is better than a fixed diameter tower; as firstly, related with D/t Ratio should be minimum as possible and should be chosen with respect to both critical buckling load and allowable buckling stress. Secondly, from maximum stresses it should have high strength at the base. Finally, by the variable thickness along the tower height, it is concluded that tapered tubular tower has high strength at the base, as it has an economical option in which reducing both material and cost.